Optimization of Urine Storage with the Addition of 40% Formalin at a Temperature of 2–8°C: Stability of the Amount and Morphology of Sediment Elements - Rusmini, Rusmini; Ridhoni, Muhammad Ahyat (Baiman Bauntung Batuah Center, 2026)
Urine sediment examination is an essential component of urinalysis used to detect various renal and urinary tract disorders. However, sediment elements in urine are prone to rapid degradation, requiring a preservation method that maintains both their quantity and morphology. This study aimed to evaluate the effect of urine storage with 40% formalin at 2–8°C for 3, 6, and 9 days on the mean count and morphology of erythrocytes, leukocytes, squamous epithelial cells, and transitional epithelial cells. A quasi-experimental design with a pretest–posttest control-group approach was used with six urine samples selected through purposive sampling. Data were analyzed descriptively, followed by repeated measures ANOVA and pairwise comparison tests. The results showed that erythrocytes (p=0.185) and transitional epithelial cells (p=0.775) did not exhibit significant differences across storage durations. Squamous epithelial cells showed significant differences in the ANOVA test (p=0.010), but the pairwise comparison did not yield consistent results. Leukocytes demonstrated significant differences in the ANOVA test (p=0.000), with a notable decrease observed on days 6 and 9 (p<0.05). Despite this, the morphology of all sediment elements remained well-preserved (score 2), with clearly distinguishable cell structures observable up to day 9. These findings suggest that urine preservation using 40% formalin at 2–8°C can maintain the count of erythrocytes, squamous epithelial cells, and transitional epithelial cells, while preserving the morphology of all four sediment elements for up to nine days. This has important implications for research requiring medium-term sample storage. The developed protocol can serve as a reference for standardizing urine preservation procedures.